The fire resistance of high-strength concrete containing natural zeolites. (February 2021) - Kushnir, Alexandra R.L.; Heap, Michael J.; Griffiths, Luke; Wadsworth, Fabian B.; Langella, Alessio; Baud, Patrick; Reuschlé, Thierry; Kendrick, Jackie E.; Utley, James E.P.
Abstract: More sustainable and environmentally friendly concretes are essential to reduce the climatic and environmental impact of the growing demand for concrete to fuel urban sprawl. This manuscript reports on an experimental study designed to test the fire resistance of one such concrete, prepared to contain natural zeolite-bearing tuff. The fire resistance of concretes containing natural zeolites has received little attention and is therefore poorly understood. Relative reductions in residual uniaxial compressive strength as a function of increasing temperature (up to 1000 °C) were very similar for the reference concrete (containing no tuff) and the tuff-bearing concrete. These data can be explained by the similar influence of high-temperature on the chemical (dehydroxylation reactions) and physical (microcracking and porosity) properties of both concretes. The satisfactory performance of the concrete containing natural zeolites following fire is welcome owing to the economic, climatic, and environmental benefits of using natural pozzolan and aggregate substitutes. Highlights: Relative decrease in strength with temperature is similar for tuff-bearing and reference concrete. Relative increase in porosity with temperature is similar for tuff-bearing and reference concrete. Relative mass loss with temperature is similar for tuff-bearing and reference concrete. Onset temperature for thermal microcracking is similar for tuff-bearing and reference concrete. Fire resistance of tuff-bearing concrete is considered satisfactory.